Effect of Economic Growth, Labor Force and Human Development Index on Unemployment in Banten Province - Kurnianto, Kholilur Rachman; Primandhana, Wiwin Priana (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2023)
To solve the macroeconomic problem of unemployment it is necessary to find a solution. Rapid changes in the labor force that are not offset by the availability of different job options will contribute to the problem of unemployment. In addition, too low a labor absorption rate will also contribute to the problem of unemployment. This research was conducted with the aim of gaining an understanding of ithe influence between economic growth (X1 ), labor force (X2), and HDI (X3 ) on unemployment (Y) in Banten Province in 2009-2020. The Central Statistics Agency (BPS), Banten Province, and the Manpower and Transmigration Service (Disnakertrans) of Banten Province all contributed secondary data used in this study. Multiple linear regression analysis with the classical assumption test, namely the Best Linear Unbiased Estimate (BLUE) was carried out with the SPSS version 25 program. This approach was chosen because it is simple and straightforward. The results showed that simultaneously all free variables affect unemployment, and partially economic growth has a negative and significant effect on unemployment. partially the labor force has a positive and significant effect on unemployment, and partially the HDI has a negative and significant effect on unemployment in Banten Province